Therapeutic observation on lung-clearing and spleen-strengthening tuina in children - Chen, Li; Wu, Xi-jun (Journal of acupuncture and tuina science, 2020)
Objective To observe the clinical efficacy of lung-clearing and spleen-strengthening tuina on exogenous cough in children. Methods A total of 77 children with exogenous cough that met the inclusion criteria were randomly divided into a treatment group and a control group according to the random number table, with 39 cases in the treatment group and 38 cases in the control group. The routine lung-clearing manipulation was used in the two groups, while the spleen-strengthening manipulation was added in the treatment group. Both groups were treated once a day, 5 times as a course of treatment. After one course of treatment, the symptom score and clinical efficacy were observed. Results There were one dropout in the treatment group and 2 dropouts in the control group. Therefore, a total of 74 cases were finally included in the analysis, with 38 cases in the treatment group and 36 cases in the control group. After treatment, there was a statistically significant difference in cough score between the two groups ( P <0.05). There was a statistically significant difference in the score of poor appetite between the two groups ( P <0.05). After treatment, the total effective rate was 89.5% in the treatment group versus 75.0% in the control group, showing a statistically significant difference ( P <0.05). Conclusion The therapeutic efficacy of lung-clearing spleen-strengthening manipulation is better than that of lung-clearing tuina manipulation alone for children with exogenous cough; regulating spleen and stomach can improve the curative efficacy of exogenous cough in children.